Duffin, Ross. W. Shakespeare’s Songbook. New York and London: Norton, 2004. 528 pp + accompanying I Audio CD. - C. Rouse, Andrew (FOCUS: Papers in English Literary and Cultural Studies, 2004)
If ever you thought you could properly evaluate a Shakespeare drama without using your ears, this is the time to finally surrender your stance and bow to the supreme orality and aurality of the Bard. As students, our “fieldweek” some thirty years ago was a long weekend at Stratford-upon-Avon, and the author of this book was raised “forty miles from the Stratford Festival in Ontario” (15). To witness my own professors (among them S.H. Burton, author of Shakespeare’s Life and Stage [1989]) rolling in the aisles at the musical version of A Comedy o f Errors was more than enough to persuade me that something magical was happening that could not be extracted from the text; in Ross Duffin’s case, theatre-going has at length resulted in the fruit of eight years of labour, Shakespeare’s Songbook, a collection of 160 songs, many of them associated with other songs contemporary with or antecedents of them.